Relationship between psychological distress and psychosomatic symptoms in obsessive-compulsive disorder patients： the mediating role of anhedonia - Li Yuhan; Song Fangqing; Wang Shaoxia; Zhang Xueting; Wang Yanrong; Fang Jianqun (Sichuan jingshen weisheng, 2025)
BackgroundObsessive-compulsive disorder （OCD） is a common neuropsychiatric illness and is listed as one of the top ten disabling conditions causing loss of income and reduced quality of life. Psychological distress is an important cause of anhedonia in OCD patients， and is closely related to psychosomatic symptoms. Therefore， exploring the role of anhedonia in the relationship between psychological distress and psychosomatic symptoms is of great significance for optimizing clinical psychological treatment protocols for OCD patients.ObjectiveTo explore the role of anhedonia in the relationship between psychological distress and psychosomatic symptoms in OCD patients， with the aim of providing references for managing psychosomatic symptoms in patients.MethodsA total of 90 patients who met the diagnostic criteria for OCD according to the International Classification of Diseases， tenth edition （ICD-10）， and who visited the Mental Health Center outpatient clinic of General Hospital of Ningxia Medical University from September 2023 to November 2024 were selected as the study objects. The instruments and techniques used for the evaluation were： Dimensional Anhedonia Rating Scale （DARS）， 10-item Kessler Psychological Distress Scale （K10） and Psychosomatic Symptom Scale （PSSS）. Model 4 of the Process for SPSS 26.0 was used to test the mediating role of anhedonia in the relationship between psychological distress and psychosomatic symptoms， with Bootstrapping used to assess the significance of mediating effect.ResultsA total of 84 patients （93.33%） completed the valid questionnaire. K10 score was positively correlated with PSSS total score， psychological symptom score and physical symptom score （r=0.559， 0.460， 0.551， P<0.01）. K10 score was negatively correlated with DARS total score （r=-0.527， P<0.01）. The total score of DARS was negatively correlated with PSSS total score （r=-0.497， P<0.01）. Anhedonia mediated the relationship between psychological distress and psychosomatic symptoms， with an indirect effect value was 0.148 （95% CI： 0.042~0.278）， accounting for 26.48% of the total effect.ConclusionPsychological distress can affect the psychosomatic symptoms in OCD patients both directly and indirectly via anhedonia.